(untitled) (Revista Iberoamericana de Bioética, 2018)
The emergence of scientific and technological advances contributed an important variety of resources to medicine; this allowed health professionals to improve the quality of care, in terms of diagnostic and therapy. But on the other hand, on occasions their use rebounded unfavorably in the patienthealth team relationship. The present work has the objective of retrospectively evaluating the implementation of new technologies and their impact on this relationship, reflecting from the perspective of bioethics, the responsibility that attributed to them in the de-humanization of medicine process.